Ali Shari’ati’s Humanism: The Interpretation of Qs. Ibrahim Verse 4 In the Context of Student’s Alignment with the Lower-Class Society - Subekti, Fiqi Restu; Muzammil, Shofiyullah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
This research discusses Ali Shari’ati’s humanism thinking in the context of students’ alignment with the lower classes, by interpreting QS. Ibrahim verse 4. Syari’ati criticised the concept of Western humanism (liberalism, marxism and existentialism) which he considered too materialistic and did not take into account the spiritual dimension of man. Instead, he offers a tawhid-based humanism that emphasises man’s role as God’s representative on earth, with the main task of freeing the oppressed from social and structural shackles. This research uses a qualitative method with a literature study approach, analysing Ali Shari’ati’s works and other supporting literature. The results show that Ali Shari’ati’s concept of humanism encourages students to act as rausyan fikr (enlightened intellectuals) who are active in social change. Student’s alignment with the lower society must be manifested in the form of advocacy, empowerment, and real action based on religious and ethical values. By understanding Ali Shari’ati’s humanism, students can develop critical awareness and act as agents of change who contribute to social justice. This article asserts that siding with the oppressed is not just a moral choice, but also part of intellectual and spiritual responsibility.